Ocena nawyków higienicznych u młodzieży w wieku licealnym = The rating of hygiene habits in people of secondary school age - Dominik Olejniczak; Katarzyna Taraś; Urszula Religioni; Aleksandra Czerw (Kazimierz Wielki University, 2015)
Olejniczak Dominik, Taraś Katarzyna, Religioni Urszula, Czerw Aleksandra. Ocena nawyków higienicznych u młodzieży w wieku licealnym = The rating of hygiene habits in people of secondary school age. Journal of Education, Health and Sport. 2015;5(8):36-46. ISSN 2391-8306. DOI 10.5281/zenodo.22426 http://dx.doi.org/10.5281/zenodo.22426 https://pbn.nauka.gov.pl/works/600221 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-43cd4092-dbdb-4b02-a7ae-2eac6e953390 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A36-46 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015.   Ocena nawyków higienicznych u młodzieży w wieku licealnym   The rating of hygiene habits in people of secondary school age   Dominik Olejniczak1, Katarzyna Taraś2, Urszula Religioni1, Aleksandra Czerw1   1Warszawski Uniwersytet Medyczny    Katedra i Zakład Zdrowia Publicznego    ul. Banacha 1a,    02-097 Warszawa   2Studenckie Koło Naukowe Zdrowia Publicznego    Warszawski Uniwersytet Medyczny    Katedra i Zakład Zdrowia Publicznego    ul. Banacha 1a,    02-097 Warszawa   Adres do korespondencji: Dominik Olejniczak Warszawski Uniwersytet Medyczny Katedra i Zakład Zdrowia Publicznego ul. Banacha 1a, 02-097 Warszawa   dominikolejniczak@op.pl Tel: 22 599 21 80 Fax: 22 599 21 81   Streszczenie   Wprowadzenie Dbanie o higienę jest istotnym elementem w życiu człowieka. Pozwala zachować zdrowie oraz zmniejsza ryzyko występowania niektórych chorób. Już od najmłodszych lat człowiek uczy się podstawowych czynności higienicznych. Z upływem lat dbanie o higienę rąk, twarzy i ciała staje się bardziej istotne. Materiał i metoda W badaniu wzięło udział 417 licealistów, w tym 226 kobiet i 191 mężczyzn. Wszyscy respondenci byli w wieku 17-19 lat, a niemal 80% z nich mieszkała w mieście powyżej 500 tys. mieszkańców. Do badania został wykorzystany autorski kwestionariusz w formie papierowej. Zawierał on 21 pytań dotyczących badanego problemu oraz 3 pytania dotyczące wieku, płci oraz miejsca zamieszkania badanych osób. Uzyskane wyniki poddano analizie statystycznej z wykorzystaniem testu Chi2 Pearsona. Za istotne statystycznie różnice uznano te, dla których prawdopodobieństwo p<0.05. Wyniki Zdecydowana większość licealistów bierze kąpiel - codziennie 60% badanych. Żaden ankietowany licealista nie kąpie się dwa razy w tygodniu. Ponad połowa 55% ankietowanych odpowiedziała, że myje włosy codziennie. Żaden z ankietowanych nie odpowiedział że w ogóle nie myje włosów. Na pytanie jak często ankietowani myją zęby, ponad połowa 54% odpowiedziała, że myje zęby dwa razy dziennie. Wnioski Zachowania higieniczne licealistów są zadowalające. Można stwierdzić, że licealiści dbają o swoją higienę osobistą. Prawie każdy z nich codziennie myje zęby oraz całe ciało. Ponad połowa ankietowanych chodzi kontrolnie do dentysty, oraz stosuje różne dodatkowe preparaty do mycia jamy ustnej, co prowadzi do poprawy stanu uzębienia. Zmniejsza prawdopodobieństwo wystąpienia w przyszłości poważniejszych problemów  z zębami.     Respondenci dbają o mycie rąk po wyjściu z toalety lub przyjściu do domu. Obniża to ryzyko zapadnięcia na infekcje i choroby, wynikające z braku zachowania higieny.   Słowa kluczowe: higiena, zachowania zdrowotne, młodzież.   Abstract   Introduction Taking care of your hygiene is a key element in human life. Allows you to stay healthy and reduce the risk of certain diseases. From an early age man learns basic personal hygiene. Over the years, taking care of the hygiene of the hands, face and body becomes more important. Matherial and methodes In the study, 417 high school students participated, including 226 women and 191 men. All respondents were aged 17-19 years, and almost 80% of them lived in the city more than 500 thousand. residents. The survey questionnaire was used author of the paper. It included 21 questions on the test problem, and three questions on age, gender and place of residence of individuals. The results were statistically analyzed using Pearson Chi2 test. The differences were considered statistically significant those for which the probability of p <0.05. Results The vast majority of high school students taking a bath - every day 60% of the respondents. No high school student respondent does not bathe twice a week. More than half of the 55% of respondents said that washing your hair every day. None of the respondents did not answer it at all does not wash hair. When asked how often respondents brush their teeth, more than half of the 54% said that brushing teeth twice a day. Conclusions Hygienic behavior of high school students are satisfactory. It can be concluded that high school students take care of their personal hygiene. Almost all of them daily brushing teeth and body. More than half of the respondents regard as controls to the dentist, and uses a variety of additional preparations for washing the mouth, which leads to the improvement of the teeth. Reduces the likelihood of future serious problems with their teeth. Respondents care about washing their hands after going to the toilet or returning home. This reduces the risk of developing infections and diseases due to lack of hygiene.   Key words: hygiene, health behaviour, young people.